Adaptive memristor-based LIF neuron circuit for energy efficient SNN crossbar array - M. S. Deepthi; H. R. Shashidhara; S. B. Rudraswamy (Cognitive Neurodynamics, 2026)

Impact of shade trees on soil aggregate stability and carbon sequestration in coffee agroforestry systems of the Western Ghats, India - Nandita Sinha; Mavinakoppa S. Nagaraja; Sonali Paul Mazumdar; S. Raghavendra; Ganapathi Guddekoppa; B. V. Champa; Deepthi Dechamma; Nurnabi Meherul Alam; Sudarshan Varma (Agroforestry Systems, 2026)

A hybrid deep learning based framework for prediction of rice yield through integration of biophysical parameters and optical remote sensing data in India - Rafath Samrin; Pundru Chandra Shaker Reddy; K. Arun Kumar; Natha Deepthi; C. Mithra; S Bhargavi Latha; Sucharitha Yadala; Gopal Kumar Thakur (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Assessing machine learning and Physics-Informed models for Multi-Lead time sea surface temperature prediction in the Arabian sea - Akshay Sunil; B. Deepthi; Muhammed Rashid; Rahul Sreedhar; Gaurav Ganjir; S. Adarsh (Stochastic Environmental Research and Risk Assessment, 2025)

Biological Decontamination of Mycotoxigenic Fusarium verticillioides Using Lactiplantibacillus plantarum MYSN128 Isolated from Traditional Vellappam: Implications for Food Safety and Global Mycotoxin Management - G. Adithi; Rakesh Somashekaraiah; B. Shruthi; S. Divyashree; N. Deepa; P. R. Vanitha; R. Vasundaradevi; B. V. Deepthi; M. Y. Sreenivasa (Current Microbiology, 2025)

Evaluation of policy interventions to mitigate the prevalence of household air pollution due to biomass fuel and its associated health risks in rural India - Yaparla Deepthi; Amit Passi; Chithra V. S; Lekshmi Mohan V; Smaranika Panda; S. M. Shiva Nagendra (Air Quality, Atmosphere & Health, 2025)

α-Glucosidase inhibitors from an endophytic fungus Edenia gomezpompae from Costus speciosus - B. M. S. Nilmini; Kavindya Samarakoon; Deepthi Yakandawala; Savitri Kumar; Nimal Adikaram; Lalith Jayasinghe; Hiroshi Araya; Yoshinori Fujimoto (Vegetos, 2025)

Healing power of Neltuma juliflora (Sw.) Raf.: a comprehensive review of its phytochemicals, pharmacology aspects, and potential health benefits - S. Deepthi; K. Narsimha; K. Ashwini; M. Sandhya Rani; K. Suresh Babu (Natural Product Research, 2025)

A deep drug prediction framework for viral infectious diseases using an optimizer-based ensemble of convolutional neural network: COVID-19 as a case study - A. S. Aruna; K. R. Remesh Babu; K. Deepthi (Molecular Diversity, 2025)

Dual Metal Ion Sensing by an Azo Compound Derived from Thiazolo[3,2-a] Indole: A Selective and Sensitive Approach - Haitham K.R. Al-Sharifi; C. B. Meenakshy; K. S. Sandhya; Ani Deepthi (Journal of Fluorescence, 2025)

Evaluating urban heat island to achieve sustainable development goals: A case study of Tiruchirappalli city, India - Deepthi S; Sudalaimani K; Radhakrishnan Shanthi Priya; Radhakrishnan S (Sustainable Cities and Society, 2024)

P21-08: Building a strategy to assess the neurotoxicity of glycol ethers - D. Pamies; S. Werner; R. Deepthi Puligilla; H. Paschoud; L. Hegg; E. Reale; M. Borgatta; J. Bertoli; C. Repond; I. Meister; T. Sajic; J. Boccard; et al. (Toxicology Letters, 2023)

Detoxification of Petroleum Hydrocarbon Contaminated Soil Through Vermicomposting and Its Impact on Gut Profile of Earthworm Eudrilus eugeniae - V. Veena; P. Kathireswari; S. Preethee; K. Saminathan; M. P. Deepthi (Water, Air, & Soil Pollution, 2023)

Modeling future irrigation water demands in the context of climate change: a case study of Jayakwadi command area, India - Akshay Sunil; B. Deepthi; A. B. Mirajkar; S. Adarsh (Modeling Earth Systems and Environment, 2021)

Genome sequencing in families with congenital limb malformations - Jonas Elsner; Martin A. Mensah; Manuel Holtgrewe; Jakob Hertzberg; Stefania Bigoni; Andreas Busche; Marie Coutelier; Deepthi C. de Silva; Nursel Elçioglu; Isabel Filges; Erica Gerkes; Katta M. Girisha; et al. (Human Genetics, 2021)
The extensive clinical and genetic heterogeneity of congenital limb malformation calls for comprehensive genome-wide analysis of genetic variation. Genome sequencing (GS) has the potential to identify all genetic variants. Here we aim to determine the diagnostic potential of GS as a comprehensive one-test-for-all strategy in a cohort of undiagnosed patients with congenital limb malformations. We collected 69 cases (64 trios, 1 duo, 5 singletons) with congenital limb malformations with no molecular diagnosis after standard clinical genetic testing and performed genome sequencing. We also developed a framework to identify potential noncoding pathogenic variants. We identified likely pathogenic/disease-associated variants in 12 cases (17.4%) including four in known disease genes, and one repeat expansion in HOXD13 . In three unrelated cases with ectrodactyly, we identified likely pathogenic variants in UBA2 , establishing it as a novel disease gene. In addition, we found two complex structural variants (3%). We also identified likely causative variants in three novel high confidence candidate genes. We were not able to identify any noncoding variants. GS is a powerful strategy to identify all types of genomic variants associated with congenital limb malformation, including repeat expansions and complex structural variants missed by standard diagnostic approaches. In this cohort, no causative noncoding SNVs could be identified.

First report of basal stem rot and blight of yardlong bean (Vigna unguiculata subsp. sesquipedalis) caused by Athelia rolfsii in India - Abdulmajeed Sajeena; Deepthi S. Nair; Teja Sri Peteti; Jacob John; Bhadra Sudha; Altharackal Vikraman Meera (Journal of Plant Pathology, 2021)

Molecular characterization and epitope-based vaccine predictions for ompA gene associated with biofilm formation in multidrug-resistant strains of A.baumannii - Deepthi Sogasu; A. S. Smiline Girija; Shoba Gunasekaran; J. Vijayashree Priyadharsini (In Silico Pharmacology, 2021)

Application of in vitro protein solubility for selection of microalgae biomass as protein ingredient in animal and aquafeed - G. Venkata Subhash; Neera Chugh; Supriya Iyer; Ashish Waghmare; Amar S. Musale; Rajesh Nandru; Rakhi Bajpai Dixit; Mahadev S. Gaikwad; Deepthi Menon; Rakesh Thorat; G.Raja Krishna Kumar; Vinod Nagle; et al. (Journal of Applied Phycology, 2020)

Drug repositioning based on the target microRNAs using bilateral-inductive matrix completion - K. Deepthi; A. S. Jereesh (Molecular Genetics and Genomics, 2020)

Non-pathogenic Fusarium oxysporum as a biocontrol agent - A. Sajeena; Deepthi S. Nair; K. Sreepavan (Indian Phytopathology, 2020)

Genetics of novel brown planthopper Nilaparvata lugens (Stål) resistance genes in derived introgression lines from the interspecific cross O. sativa var. Swarna × O. nivara - S. Akanksha; V. Jhansi Lakshmi; Arun Kumar Singh; Yamini Deepthi; P. M. Chirutkar; Ramdeen; Divya Balakrishnan; N. Sarla; S. K. Mangrauthia; T. Ram (Journal of Genetics, 2019)

Multifractal characterization of meteorological drought in India using detrended fluctuation analysis - S. Adarsh; D. Nagesh Kumar; B. Deepthi; G. Gayathri; S. S. Aswathy; S. Bhagyasree (International Journal of Climatology, 2019)
This study presents multifractal detrended fluctuation analysis (MF‐DFA) to describe the multifractality of Standardized Precipitation Index (SPI) series from 30 meteorological subdivisions of India estimated at different aggregation timescales (3, 6 and 12 months) based on long‐term monthly rainfall data sets of 1871–2016 period. The plots of fluctuation function and generalized Hurst exponents confirmed that multifractality is evident in most of the SPI series; however, it is found that its strength and persistency differ with timescale and space. The Hurst exponents of long‐term (SPI‐12) and medium‐term (SPI‐6) drought series of all subdivisions showed long‐term persistence irrespective of the climatic conditions of the region, while the short‐term droughts (SPI‐3) of six subdivisions displayed short‐term persistence. Further, the analysis by partitioning the data to four time spells: 1871–1905, 1906–1940, 1941–1975 and 1976–2016 showed that the persistency of long‐ and medium‐term drought is rather permanent. The analysis on changes in multifractal properties with respect to the climatic shift of 1976/1977 period showed that there is a clear increase in multifractal properties of all types of drought series in the recent past (post‐1976 period). This study also finds that the Hurst exponents and degree of multifractality of all types of droughts increase with increase in aggregation timescales. The multifractality of all the long‐term drought series (SPI‐12) and most of the SPI‐6 series are found to be due to correlation properties, while that of SPI‐3 is because of joint effect of correlation properties and the broadness of probability distribution.

Antiaflatoxigenic Potential of Cell-Free Supernatant from Lactobacillus plantarum MYS44 Against Aspergillus parasiticus - K. Poornachandra Rao; B. V. Deepthi; S. Rakesh; T. Ganesh; Premila Achar; M. Y. Sreenivasa (Probiotics and Antimicrobial Proteins, 2019)

A pharmacokinetic comparison of homodimer ARB-92 and heterodimer ARB-89: novel, potent antimalarial candidates derived from 7β-hydroxyartemisinin - Bonnie A. Avery; Deepthi Pabbisetty; Lie Li; Abhisheak Sharma; Mahesh K. Gundluru; Amar G. Chittiboyina; John S. Williamson; Mitchell A. Avery (Journal of Pharmaceutical Investigation, 2018)

Grain Size Analysis for Elucidation of Depositional Environment of Kalpakkam, India - K. Deepthi; Usha Natesan; A. L. Muthulakshmi; Vincent A. Ferrer; S. V. Narasimhan; V. P. Venugopalan (Environmental Processes, 2018)

A comparative proteome assay on the quality of yardlong bean pods as influenced by the organic and inorganic nourishment systems - Deepthi K. Kumar; Deepu Mathew; P. A. Nazeem; P. S. Abida; C. George Thomas (Acta Physiologiae Plantarum, 2017)

Enhanced camptothecin production induced by elicitors in the cell suspension cultures of Ophiorrhiza mungos Linn. - S. Deepthi; K. Satheeshkumar (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Mineralogical Characterization in the Marine Environment of Kalpakkam, Southeast Coast of India - K. Deepthi; U. Natesan; A. L. Muthulakshmi; V. A. Ferrer; V. P. Venugopalan; S. V. Narasimhan (Marine Georesources & Geotechnology, 2015)

Monitoring Chlorophyll – a Concentration in the Coastal Waters of Kalpakkam (India): Application of a Regional Algorithm using Oceansat – 2 Ocean Colour Monitor - Usha Natesan; Vincent A Ferrer; Arvind Sahay; Prakash Chauhan; A. L. Muthulakshmi; K. Deepthi; V. P. Venugopalan; S. V. Narasimhan (Journal of the Indian Society of Remote Sensing, 2015)

The prospects for hybrid rice in India - David J. Spielman; Deepthi E. Kolady; Patrick S. Ward (Food Security, 2013)

Textural and depositional processes of surface sediments of Kalpakkam, Southeast Coast of India - Usha Natesan; K. Deepthi; A. L. Muthulakshmi; Vincent A. Ferrer; S. V. Narasimhan; V. P. Venugopalan (Frontiers of Earth Science, 2012)

Plasmid-Mediated Biodegradation of the Anionic Surfactant Sodium Dodecyl Sulphate, by Pseudomonas aeruginosa S7 - Deepthi Yeldho; Sharrel Rebello; M. S. Jisha (Bulletin of Environmental Contamination and Toxicology, 2011)

The lipid peroxidation induced changes of protein in refrigerated yellowtail minced meat - Deepthi M. S. MUNASINGHE; Takeshi OHKUBO; Tadashi SAKAI (Fisheries Science, 2005)